2014
DOI: 10.1037/neu0000064
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of cognitive impairment following adult cancer chemotherapy.

Abstract: Objective: Chemotherapy-induced cognitive impairments are reported by many cancer survivors. Research to date has not provided a clear description of their nature, extent, mechanisms, and duration. To investigate the impairments and factors that could influence their identification and severity, the present meta-analysis brings together research on this topic in adult cancer patients. Method: Our random-model meta-analysis includes 44 studies investigating the cognitive performance of adults treated with chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 50 publications
(97 reference statements)
4
66
0
3
Order By: Relevance
“…A recent metaanalysis [2] showed a decrease in capacity of attention and selective attention as well as in immediate and delayed verbal recall in patients treated with chemotherapy compared to healthy persons. Changes observed during neuropsychological testing are corroborated by the results of neuroimaging studies carried out in the recent years [318].…”
Section: Introductionmentioning
confidence: 99%
“…A recent metaanalysis [2] showed a decrease in capacity of attention and selective attention as well as in immediate and delayed verbal recall in patients treated with chemotherapy compared to healthy persons. Changes observed during neuropsychological testing are corroborated by the results of neuroimaging studies carried out in the recent years [318].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive sequelae of chemotherapy have been demonstrated by objective and validated neuropsychological tests [3,6] with incidences ranging from 19% to 78% across different studies [3]. Cognitive domains that were most likely to be affected included learning, memory, processing speed and executive function.…”
mentioning
confidence: 99%
“…Cognitive alterations are among the most common symptoms related to cancer (Janelsins et al, 2011). Evaluations of overall cognitive functioning as well as immediate free recall, delayed memory, verbal memory, selective attention, attention span, and abstract reasoning indicate deterioration during and after breast cancer-treatment-related procedures (Lindner et al, 2014;Biglia et al, 2012;Vearncombe et al, 2009;Ando-Tanabe et al, 2014). Härtl et al, (2010) found out that after a mastectomy and with the passage of time, all QLQ-C30 functioning scales improve, except cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%